2021
DOI: 10.1007/s40857-021-00245-2
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Effect of Face Mask Design and Material Choice

Abstract: The widespread adoption of face masks is now a standard public health response to the 2020 pandemic. Although studies have shown that wearing a face mask interferes with speech and intelligibility, relating the acoustic response of the mask to design parameters such as fabric choice, number of layers and mask geometry is not well understood. Using a dummy head mounted with a loudspeaker at its mouth generating a broadband signal, we report the acoustic response associated with 10 different masks (different mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In general, the insertion losses are in line with the attenuations that others have found. [8][9][10][13][14][15][16] In our measurements, one transparent mask offers virtually no insertion loss: the face mask with a cling film insert and honeycomb support. The insertion loss at higher frequencies is also considerably less than any transparent masks measured by others.…”
Section: First Mannikin Experiments On Masks Comparing Different Clea...mentioning
confidence: 79%
See 1 more Smart Citation
“…In general, the insertion losses are in line with the attenuations that others have found. [8][9][10][13][14][15][16] In our measurements, one transparent mask offers virtually no insertion loss: the face mask with a cling film insert and honeycomb support. The insertion loss at higher frequencies is also considerably less than any transparent masks measured by others.…”
Section: First Mannikin Experiments On Masks Comparing Different Clea...mentioning
confidence: 79%
“…The attenuation of the sound was most significant about 2000 Hz. Balamurali et al 14 used a mannikin made from thick heavy epoxy with a small loudspeaker mounted in the mouth to measure ten opaque masks. The attenuations ranged from 0 to 5 dB from 1000 to 3000 Hz with many masks also showing a significant increase in sound loss above 3000 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…also found no significant difference in recognizing words with the surgical mask in quiet conditions ( Mendel et al., 2008 ). The attenuation effect (ranging from 3 to 12 dB) of medical and N95 masks on the speech signal in the high-frequency region (above 1 kHz) may be the contributing factor to decreased word recognition ability (Ryan M Corey et al., 2020 , Wolfe et al., 2020 ; Balamurali BT et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Face masks can result in detrimental effects on verbal communication and speech intelligibility by occluding important visual cues from mouth and lip gestures, interfering with natural articulatory movements, and altering speech acoustic features ( McGurk, 1976 ; Bond et al., 1989 ; Murthy et al., 1995 ; Wieczorek, 2013 ; Palmiero et al., 2016 ). Recent studies on the acoustic effect of masks on speech signals have reported that masks serve as a low-pass filter and the high-frequency range (above 1 kHz) of spoken speech is primarily attenuated by 3–4 dB with a simple medical mask and close to 12 dB with the N95 masks ( Corey et al., 2020 ; Wolfe et al., 2020 ; Balamurali BT et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the material has more impact on sound transmission than the geometric shape and design of the mask [ 31 , 32 ]. It seems that in order to improve some characteristics affecting the protection efficiency and usability of face masks, new technologies should be used.…”
Section: Discussionmentioning
confidence: 99%